Immunization Servis Mobile Information System at Posyandu Medan Sunggal - Batubara, Umar Said; Nasution, Muhammad Irwan Padli (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Posyandu (Integrated Health Service Post) is a form of community-based health effort. The flow of the management process that occurs at the Posyandu in Medan Sunggal District is where each Posyandu participant visits the location, then the cadres serve the registration, after that they can provide services at the Posyandu. Examination of toddlers generally starts from zero to five years of age, services for toddlers based on weight and height are then given immunizations and vitamin A. There are five types of immunizations for toddlers, including measles, hepatitis, B.C.G, D.P.T, and polio. The ongoing process still raises problems such as errors by cadre officers in recording registration and errors in recording participant services and recording reports which take a long time. Based on the constraints faced in the field, it is necessary to have innovations related to immunization services. This study describes the context of a mobile-based Posyandu information system in Medan Sunggal. The results of the development of this application are presented in more detail in this article.